The Effect of Financial Performance on Audit Delay: A Case Study of Non Cyclical Companies Listed on The IDX - Suseti, Dina Anggraeni; Wahyuningtyas, Endah Tri (Jurnal Akuntansi, 2025)
Audit delay, the delay between the fiscal year closing date and the date of issuance of the audit report by an independent auditor, is a significant issue that can impact the relevance and reliability of financial information for stakeholders such as investors, creditors, and regulators. Although companies in non-cyclical sectors such as food, beverages, and staple goods generally have stable revenues, audit delays still frequently occur, including in the 2021–2023 period in the Indonesian capital market. This indicates that sector stability does not guarantee the timely submission of audited annual financial statements. This study aims to analyze the effect of financial performance on audit delay in non-cyclical companies listed on the Indonesia Stock Exchange (IDX). Financial performance is operationalized through three main indicators: Price to Earnings Ratio (PER), Net Profit Margin (NPM), and Current Ratio (CR). PER reflects market perception of a company's valuation and profit growth prospects, NPM indicates efficiency in generating profits from sales, while CR measures a company's ability to meet short-term obligations. It is hoped that the results of this study can provide a deeper understanding of the internal company factors that influence audit delay, especially in sectors that are considered relatively financially stable.